Regulating NKX3.1 stability and function: Post‐translational modifications and structural determinants. Issue 6 (4th February 2016) - Padmanabhan, Achuth; Rao, Varsha; De Marzo, Angelo M.; Bieberich, Charles J.
Abstract : BACKGROUND: The androgen‐regulated homeodomain transcription factor NKX3.1 plays roles in early prostate development and functions as a prostate‐specific tumor suppressor. Decreased expression of NKX3.1 protein is common in primary prostate cancer. Discordance between NKX3.1 mRNA and protein levels during prostate carcinogenesis suggested a key role for post‐transcriptional modifications in regulating NKX3.1 protein levels in prostate epithelial cells. Subsequent studies revealed NKX3.1 to be modified post‐translationally at multiple sites. METHODS: We reviewed published literature to identify and summarize post‐translational modifications and structural elements critical in regulating NKX3.1 stability and levels in prostate epithelial cells. RESULTS: NKX3.1 is modified post‐translationally at multiple sites by different protein kinases. These modifications together with several structural determinants were identified to play an important role in NKX3.1 stability and biology. CONCLUSIONS: In this review, we provide a comprehensive overview of the known post‐translational modifications and structural features that impact NKX3.1. Defining factors that regulate NKX3.1 in prostate epithelial cells will extend our understanding of molecular changes that may contribute to prostate cancer initiation and progression. Prostate 76:523–533, 2016 . © 2016 Wiley Periodicals, Inc.